2013
DOI: 10.1155/2013/802734
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Can Protect against Vanadium-Induced Lipid Peroxidation in the Hepatic Tissue

Abstract: The protective effect of magnesium as magnesium sulfate (MS) on sodium-metavanadate- (SMV-) induced lipid peroxidation (LPO) under in vivo and in vitro conditions was studied. The 18-week SMV intoxication (Group II, 0.125 Vend/mL) enhanced spontaneous malondialdehyde (MDA) generation in rat liver, compared with the control (Group I) and MS-supplemented animals (Group III, 0.06 Mgend/mL). Coadministration of SMV with MS (Group IV, SMV-MS) caused a return of the MDA level to the control value range. The effect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
(42 reference statements)
1
21
0
Order By: Relevance
“…Free radicals in DM cause peroxidative breakdown of phospholipids that lead to accumulation of MDA [51]. Agnieszka et al, have been shown that magnesium intake for 18 weeks could prevent lipid peroxidation stimulated by vanadium in hepatic tissue [52]. Thus, from our results it is seemed that magnesium may show an antioxidant activity through preventing lipid peroxidation in renal tissue that is indicated by a decrease in kidney MDA level.…”
Section: Discussionsupporting
confidence: 53%
“…Free radicals in DM cause peroxidative breakdown of phospholipids that lead to accumulation of MDA [51]. Agnieszka et al, have been shown that magnesium intake for 18 weeks could prevent lipid peroxidation stimulated by vanadium in hepatic tissue [52]. Thus, from our results it is seemed that magnesium may show an antioxidant activity through preventing lipid peroxidation in renal tissue that is indicated by a decrease in kidney MDA level.…”
Section: Discussionsupporting
confidence: 53%
“…Some authors have found these values to decrease, while others report them unchanged. It has been observed that V produces peroxidative changes in the erythrocyte membrane and liver (Scibior et al, 2006(Scibior et al, , 2013. However, other authors have found no such changes (Dai et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…19 In vitro studies, in turn, showed the effect of orthovanadate, metavanadate, decavanadate and the influence of some oxidovanadium(IV) complexes on bone resorption, bone matrix formation and mineralization, cellular proliferation of normal and tumoural osteoblasts, cell differentiation of tumoural osteoblast, production of type-I collagen, macrophages, and on the bone DNA, collagen, and non-collagen protein (NCP) synthesis. Generally, the consequences of the V-Mg interaction on health are relatively little known, and the data referring to the interaction between the above-mentioned elements (except our studies) [50][51][52][53][54][55][56] are limited. 30 In addition, several studies on the effects of V on bone tissue, conducted both under in vivo and in vitro conditions, yielded possible mechanisms of its action in bone.…”
Section: Introductionmentioning
confidence: 77%
“…56 The influence of the 18 week administration of V and Mg (as SMV and MS) separately or together on lipid peroxidation (LPO) in the rat hepatic tissue has also been published. 55 In all the above-mentioned reports the effects of the mutual interaction between V and Mg were presented.…”
Section: Discussionmentioning
confidence: 99%